(3TQM Ydi efXheI aj Yde GdfMhs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY cdeI GdESdGe hHYO abO SCdfi CYR GdCMHGH Cf CVY TQMkG dWja Ydi GdJi hVYgG ai bhGYO GdfMh s
(3BNQgG (B:s
(3CTGQ Hbhdg hcGf Ydjg Cf jbhd hCTHGg Ef s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3GdfSNI HgG MhGTs
(3fMh(B,s
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs